2023
DOI: 10.3390/su15118717
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Characterization and Measurement of the Carbonaceous Fraction of Particulate Matter

Mauricio A. Correa-Ochoa,
Roxana Bedoya,
Luisa M. Gómez
et al.

Abstract: The carbonaceous particles represent a significant fraction in the particulate matter (PM) and are considered an environmental hazard due to their effects on climate and health. The main goal in this research is to identify and analyze the scope that have been achieved so far on the characterization and measurement of the carbonaceous fraction present in PM, a great contribution to global pollution and thus to the deterioration of public health. The ProKnow-C methodology was used to build a bibliographic portf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 151 publications
(138 reference statements)
0
0
0
Order By: Relevance
“…Studies in urban areas have revealed that water-soluble inorganic ions are major components of fine particles and might generally contribute up to 50% [8]. Carbonaceous materials also contribute to a large fraction of PM 2.5 concentrations in the atmosphere [8][9][10]. Carbonaceous species are chemically divided into elemental carbon (EC) and organic carbon (OC).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in urban areas have revealed that water-soluble inorganic ions are major components of fine particles and might generally contribute up to 50% [8]. Carbonaceous materials also contribute to a large fraction of PM 2.5 concentrations in the atmosphere [8][9][10]. Carbonaceous species are chemically divided into elemental carbon (EC) and organic carbon (OC).…”
Section: Introductionmentioning
confidence: 99%